Cross-sectional Areas of the Thoracic Aorta in Children and Adolescents With Repaired Tetralogy of Fallot Obtained by Cardiac Magnetic Resonance Angiography. Issue 2 (March 2018) - Gräfe, Daniel; Gutberlet, Matthias; Mende, Meinhard; Dähnert, Ingo; Lücke, Christian; Kostelka, Martin; Nitzsche, Stefan; Hoffmann, Janine; Grothoff, Matthias
Abstract : Purpose: Dilatation of the thoracic aorta is a well-known finding in corrected Tetralogy of Fallot. Complications are rare but can be life-threatening. Standard 1-dimensional (1D) measurements have several limitations. We sought to establish contrast-enhanced magnetic resonance angiography cross-sectional areas of the aorta that could serve as reference values and to identify parameters that are associated with aortic dilatation. Materials and Methods: We enrolled 101 children and adolescents. The aortic areas were measured at the level of the aortic sinus (AS), the sinotubular junction (STJ), the ascending aorta (AA), the brachiocephalic trunk (TBC), and the descending aorta (DA). Sex-specific aortic dimensions were presented as percentile curves as well as regression equations. Furthermore volumetric and functional parameters as well as clinical data were analyzed to identify parameters that are associated with aortic dilatation. Results: Aortic areas (mm 2 ) for female subjects were 139+366×body surface area (BSA) for the AS, 134+255×BSA for the STJ, 113+239×BSA for the AA, 88+185×BSA proximal to the TBC, and 2.9+88×BSA for the DA. Aortic areas (mm 2 ) for male subjects were 162+403×BSA for the AS, 171+258×BSA for the STJ, 151+233×BSA for the AA, 73+206×BSA proximal to the TBC, and 21+80×BSA for the DA. The postoperative interval and age at examination were parameters associated with aortic size. Conclusions: We provide aortic areas in children and adolescents after correction of Tetralogy of Fallot measured by contrast-enhanced magnetic resonance angiography. Our 2D data may better depict the geometry of enlarged aortae than standard 1D diameters and serve as reference values for evaluating aortic disease in these patients.